The effects of boxing training on the physical condition of first-year students - Tikhonov Yu.V. ,; Karpov V.Yu. ,; Yurchenko A.L. ,; Tagirova N.D. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the intensity of the physical response of first-year students to boxing training during the initial phase. Methods and structure of the study. Thirty-two young men were chosen from the student population at the university, creating two groups of young students. One group consisted of 18 individuals who began boxing training, while the other group included 14 individuals who did not wish to participate in sports. These individuals were monitored for a period of one year. The study employed a method of testing and a method of statistical analysis. Results and conclusions. The boxing classes enhanced physical activity and boosted endurance among participants. The students' stamina improved, enabling them to handle greater loads. The boxing regimen enriched the repertoire of learned movements, enhanced speed and power, and refined the coordination of those involved.